2021
DOI: 10.1164/rccm.202103-0548oc
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Dynamics of a Blood Transcriptomic Signature of Tuberculosis

Abstract: including recruitment, clinical management, and data collection. ME, LJ, RR and ON processed RNA samples and performed the RISK11 assay. MN, SM and JVH processed and performed the respiratory pathogens PCR assay. HM, SKM, KH, CH, MM, NB, and ME provided operational or laboratory support and project management. HM, MM, SCM, SAK, MH, and TJS analysed data, interpreted results, and wrote the first draft of the manuscript. All authors had full access to the data, and reviewed, revised, and approved the manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Our findings of lower RISK6 score among participants who had already completed IPT are consistent with the CORTIS-HR trial where people with HIV who were RISK11 negative were more likely to have received IPT at enrollment compared with those who were RISK11 positive [16]. However, our findings differ from a longitudinal analysis of CORTIS [30], which found no difference in RISK11 conversion or reversion frequencies between those on IPT at enrollment, those who started IPT during a 3-month period, and IPT-naive participants. Potential explanations for this discordance in results could be that RISK11 responses require time after the completion of IPT or differences in TB prevalence between the study settings.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings of lower RISK6 score among participants who had already completed IPT are consistent with the CORTIS-HR trial where people with HIV who were RISK11 negative were more likely to have received IPT at enrollment compared with those who were RISK11 positive [16]. However, our findings differ from a longitudinal analysis of CORTIS [30], which found no difference in RISK11 conversion or reversion frequencies between those on IPT at enrollment, those who started IPT during a 3-month period, and IPT-naive participants. Potential explanations for this discordance in results could be that RISK11 responses require time after the completion of IPT or differences in TB prevalence between the study settings.…”
Section: Discussionsupporting
confidence: 80%
“… Triage Collection method and not a test itself - Studies are few and heterogenous, no pooled performance estimates exist - Ultra applied to a single swab had a sensitivity of 88% in outpatients 41 but only 43% sensitivity when used for active case finding in a prison 40 - TB-LAMP 42 applied to oral swabs had sensitivities ranging from 33-50% - FLOQSwabs (Copan Italia) preferred 41 - Self-swabbing, comparable to health worker-administered swabs for other pathogens 44 , appears feasible - Potential for paediatric TB 43 - Insufficient Mtb may be recovered from swabs in patients with low sputum bacillary load 40 - Performance of novel assays (e.g., next-generation LAM and NAATs unknown) may overcome sensitivity limitations associated - Optimal number of swabs, swab design, and the processing method are under evaluation and may improve the release of material from swabs -No tests purpose-built for tongue swabs yet exist Blood Host transcriptome mRNA blood signatures associated with the immune system's response to Mtb have shown promise for diagnosis. 68 Triage Xpert Host Response (Cepheid) - A multicentre study showed 90% sensitivity and 86% specificity 64 -Other studies have shown lower specificities (26% 101 , 53% 102 ) at >90% sensitivity - Limited data with small numbers of cases, however, multicentre studies are emerging - Xpert HR has the most data available - RNA is labile and, for Xpert HR, time from blood collection to testing must be <30 min and stabilisation agents may be required - Cost unclear, but likely high - Potential utility treatment response monitoring, management of diseases other than TB (signature-positive patients without TB could have other infections 95 ), and false-positive TB PCR results 65 , which are frequent in people with previous TB 68 , 84 , 103 - Signatures (including Sweeney3 in Xpert HR) measured using ultra-sensitive methods (sequencing, Nanostring) 68 struggle to meet WHO TPPs 65 , 66 ...…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“…Even the most promising triage tests (CRP, host transcriptome signatures) have specificity limitations, since other conditions (viral infections, cancers) can produce readouts that may resemble TB, 95 which impact implementation potential given that triage test specificity is the primary cost driver. 96 Hence, with the introduction of novel tests, a negative test in a triage-positive person should inform further non-TB diagnostic decision making to justify these tools' cost.…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“… 45 A recent longitudinal study also showed a transient increase in transcriptomic signatures (RISK11) possibly due to viral infections. 61 Other communicable diseases like malaria or COVID-19 and non-communicable diseases like diabetes can affect the performance of host mRNA signatures but this has been insufficiently studied. 62 , 63 , 64 Thus, it is critical that any new signatures are designed in such a way as to allow differentiation of TB from viral and other infections, for example through the exclusion of ISGs and the use of multinominal modelling.…”
Section: Methodsmentioning
confidence: 99%